The Research on Creative Design of Bai Architectural Decoration Patterns in Jianchuan Based on KANO Model Analysis - Xiao, Zhenping; Mayusoh, Chanoknart; Inkuer , Akapong (Journal of Roi Kaensarn Academi, 2024)
The objectives of this research were:1)Discover the relationship between decorative cultural and creative design elements of Jianchuan Bai folk houses and user satisfaction; 2) Compare the design priorities of the attributes of decorative cultural creative design elements of Jianchuan Bai folk houses;3) Propose creative design of decorative patterns for Bai folk houses in Jianchuan Methods and product application scenarios. the sample was interviewed by Jianchuan craftsmen, designers and travelers in the Dali area.They were selected by Questionnaire Star collected 103 valid questionnaires,the research instrument for the data collection were KONO Model . The research results were found as traditional architectural decoration is transformed into user needs of modern design products:1) The priority of the design elements of Jianchuan Bai folk house decoration cultural creative products is "the product is portable" > "the product embodies the expanded application of Jianchuan Bai folk house decoration function" > "the product has connotation and meaning ” > “Products embody regional characteristics” > “Products embody regional auspicious culture” > “Products embody regional decorative patterns” > “Products embody regional cultural themes” ;2) The factors of “regional characteristic patterns” are attractive attributes and “regional characteristics auspicious meanings” The "factor" is the desired attribute, and the "function expansion" factor is the necessary attribute.3) Regional characteristics affect consumers’ purchasing judgment. Based on this, the researchers established the sample extraction scope and product functional uses for creative pattern design. The research results will provide evidence-based reference for the Jianchuan Bai folk residential decoration culture to propose creative design solutions that can meet the needs of contemporary users, and contribute a small amount to drive the development of local cultural industries and promote the revitalization of local traditional culture.